Rheumatology Symptoms and Syndromes - Benenson, Efim.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
Rheumatology: Symptoms and Syndromes organizes the rheumatic diseases in the form of syndromes as stable combinations of symptoms, and links these to morphological manifestations. This presentation of the rheumatic diseases provides a pedagogical framework for differential diagnosis in rheumatology. To further aid the teacher and student, Professor Efim Benenson provides algorithms of clinical reasoning based on morphology and pathophysiology. Professor Benenson$1 (Bs practice-oriented, didactic approach, and innovative organization of the rheumatic diseases is a valuable diagnostic aid to practicing rheumatologists and those teaching or training in rheumatology. Readers are recommended the companion book, Rheumatology: Clinical Scenarios, for further reading on Professor Benensons's organization of the rheumatic diseases.s
Section I: Articular and Musculoskeletal Disorders -- Articular Disorders -- Diseases of the Spine -- Soft-Tissue Rheumatism and Related Disorders -- Regional Arthrological and Musculoskeletal Syndromes -- Paraneoplastic Syndromes (PNS) in Rheumatology -- Algorithms in Articular and Musculoskeletal Disorders -- Section 2: Connective Tissue Disease (CTD) and Vasculitis Systemic Diseases in Rheumatology -- General Symptoms -- Involvement of Connective Tissue Structures -- System/Organ Involvement -- (Auto) Immunological Phenomena and Serological Diagnostics -- Treatment-Induced and Associated Conditions and Diseases -- Algorithms for Connective Tissue Diseases and Vasculitis.
Keywords: Medicine; Dermatology; Internal medicine; Rheumatology; Medicine & Public Health; Rheumatology; Internal Medicine; Dermatology